2014
DOI: 10.1177/1077801214557955
|View full text |Cite
|
Sign up to set email alerts
|

A Border Context of Violence

Abstract: Female sex workers (FSW) represent a population confronted with an array of intersecting social problems. We explore the case of FSW in Nuevo Laredo and Ciudad Juarez to understand the everyday violence associated with sex work within the unique context of Mexico. Life history interviews were conducted with 109 FSW revealing violent acts by clients and other sex industry employees (bar owners, police, other FSW). The risk of violence by different types of persons associated with the sex work industry varied by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 48 publications
1
30
0
3
Order By: Relevance
“…Juarez’s downtown area, known as the Zona Centro . 19 The Zona Centro is a commercial zone for the whole city, not just sex work. The bars and hotels where most of the sex work is done are scattered between markets, hair salons, restaurants, and other retail shops.…”
Section: Methodsmentioning
confidence: 99%
“…Juarez’s downtown area, known as the Zona Centro . 19 The Zona Centro is a commercial zone for the whole city, not just sex work. The bars and hotels where most of the sex work is done are scattered between markets, hair salons, restaurants, and other retail shops.…”
Section: Methodsmentioning
confidence: 99%
“…Addressing violence against FSWs is a global public health priority [10]. FSWs routinely encounter both intimate partner violence and gender-based violence [10][11][12][13]. In the context of FSWs' lives, violence is not only initiated by clients and non-commercial partners, but other key actors in the sex work industry also commit such abusive acts, namely bar owners, police, and even other FSW [12].…”
Section: Introductionmentioning
confidence: 99%
“…FSWs routinely encounter both intimate partner violence and gender-based violence [10][11][12][13]. In the context of FSWs' lives, violence is not only initiated by clients and non-commercial partners, but other key actors in the sex work industry also commit such abusive acts, namely bar owners, police, and even other FSW [12]. For FSWs working at geographic borders, financial need is often a major motivation to initiate sex work; in fact, many women that engage in commercial sex work are mothers with limited options for work, making the sex work industry a pathway to financial independence [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Tijuana, women engaging in survival sex face an array of social problems that impede them from finding community. Research findings have indicated that two-thirds of women along the Mexico-U.S. border may be confronted by violent encounters with clients [6]. Drug use is also common within this population, and those who inject drugs have a high prevalence of STIs [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%